Which factors determine the success of strategic niche developments?. Issue 1 (2014) - ,
<x xml:space="preserve">Abstract</x> Purpose – The study's purpose is to review and discuss limitations of "strategic niche management" (SNM) success factors in relation to the experiences of an enterprise network to improve niche development for integrated design concepts. Design/methodology/approach – The emergence of a successful passive house innovation network in the Flemish Region is described. The innovation journey of the network is related to success factors detected in SNM literature regarding market niche development. Findings – The study identifies additional success factors for systemic innovation, such as involving small‐ and medium‐sized innovators and demonstration projects and using a dedicated regional enterprise network. Research limitations/implications – The qualitative analysis specifically reflected on SNM success factors such as envisioning, learning, and network composition and formation. The study confirms the importance of these success factors by means of one detailed innovation journey. It identifies additional success factors and discusses opportunities to improve the relation of SNM literature with other seminal fields. Practical implications – Government seed money is important in providing a breakthrough in enterprise network initiatives. A focus on architectural innovation instead of technology innovation is to be preferred for stimulating integrated design concepts. Originality/value – The paper addresses the relevance and limitations of SNM success factors during the formation of enterprise networks. The study shows how an integrated design approach was used to cluster innovation opportunities and to inspire innovation development and collaboration for know‐how development between multiple players. <ack> <x xml:space="preserve">Acknowledgements</x> The author wishes to thank the three anonymous reviewers for their valuable comments and reflections. </ack>